Nail Changes During Docetaxel Containing Combination Chemotherapy - Woo, In Sook (Korean Association of Internal Medicine, 2004)
Nail toxicity following systemic chemotherapy is common. Onychopathy during the period of neutropenia following chemotherapy may cause subungual abscesses and serious infection. Despite taxoid-related toxicity being increasingly reported since 2000, there are still phase II systemic chemotherapy studies using taxoid that have never mentioned nail changes. Recently, new criteria for the evaluation of nail toxicity have been suggested. The present report is the first of its kind, in Korea, to describe a case of docetaxel-associated onychopathy, which improved following a reduction in the docetaxel dose.